पश्चिमी राजस्थान में देशज इतिहास-लेखन का संक्रांति काल एवं क्षेत्रीय इतिहास का विमर्श - Amarawat, Vikram Singh; Jyotsna (Vidyapith (વિદ્યાપીઠ), 2020)
There is a close relationship between indigenous historiography and regional history. The time of the nineteenth century can be considered as the peak period of indigenous historiographical traditions developed in India. In western Rajasthan, the writings based on the perception of the past can be considered as part of this indigenous historiographical tradition. The earliest mention of the of the compositions named Khyat is found: ninth century, but the first such type of composition found only in the sixteenth century . In the present article, attempt has been made to understand these texts in the context of indigenousness. A brief survey of the Khyat literature from the sixteenth century to the first half of the nineteenth century has been presented. The changes in these Khyats in the Second half of the nineteenth century can be called the transition phase. The article also analyses how the Khyats written during this transition phase are different from those written in the past. The discourse of regional history is currently one of the new debates in historiography. In this context, an attempt has been made in this article to understand the indigenous historiographical tradition of western Rajasthan. देशज इतिहास-लेखन एवं क्षेत्रीय इतिहास-लेखन के बीच एक घनिष्ठ संबंध रहा है। उन्नीसवीं सदी का समय भारत में विकसित हुई देशज इतिहास-लेखन परम्पराओं का चरम काल कहा जा सकता है। पश्चिमी राजस्थान में अतीत के बोध के आधार पर लिखी गई ख्यातों को इसी देशज इतिहास लेखन परम्परा का हिस्सा माना जा सकता है। ख्यात नामक रचनाओं का प्रारम्भिक उल्लेख नवमी में प्राप्त होता है, किन्तु इस तरह की रचनाएं सबसे पहले सोलहवीं सदी में ही प्राप्त होती है। प्रस्तुत शोध पत्र में इन रचनाओं को देशजता के दर्भ में समझने का प्रयास किया जाएगा। सोलहवीं सदी से उन्नीसवीं सदी के पूर्वार्द्ध तक की ख्यातों का एक संक्षिप्त सर्वेक्षण प्रस्तुत किया जाएगा। ख्यात लेखन परम्परा में उन्नीसवीं सदी के उत्तरार्द्ध में हुए बदलाव को संक्रांति काल कहा जा सकता है। इस संक्रांति काल में जो ख्यातें लिखी गई वो पूर्व में लिखी गई ख्यातों से किस तरह से भिन्न है, इसका एक विश्लेषण किया जाएगा । क्षेत्रीय इतिहास का विमर्श वर्तमान में इतिहास लेखन की नई बहसों में से एक है। इसी संदर्भ में पश्चिमी राजस्थान की देशज इतिहास लेखन परम्परा और उसमें हुए बदलावों को समझने का प्रयास इस आलेख में किया जाएगा ।